2019
DOI: 10.3390/ijerph16050706
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Heavy Episodic Drinking: A Random Survey of 18 to 34-Year-Olds in Four Cities in Four Different Continents

Abstract: Background: Heavy episodic drinking (HED) can have health and social consequences. This study assesses the associations between HED and demographic, socioeconomic, motivation and effects indicators for people aged 18–34 years old living in four cities in different regions of the world. Method: Multistage random sampling was consistent across the four cities (Ilorin (Nigeria), Wuhan (China), Montevideo (Uruguay) and Moscow (Russia)). The questionnaire was forward/back translated and face-to-face interviewing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The authors were able to identify only two non-school-based studies of drinking motives among Chinese young adults. A cross-country (Nigeria, China, Uruguay, and Russia) survey of heavy episodic drinkers between 18-34 years of age found that the motivations for drinking differ greatly in each location [38]. It was noted that drinkers from Wuhan, China, were more likely to associate heavy drinking with negative consequences, such as aggression, as compared with the other regions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors were able to identify only two non-school-based studies of drinking motives among Chinese young adults. A cross-country (Nigeria, China, Uruguay, and Russia) survey of heavy episodic drinkers between 18-34 years of age found that the motivations for drinking differ greatly in each location [38]. It was noted that drinkers from Wuhan, China, were more likely to associate heavy drinking with negative consequences, such as aggression, as compared with the other regions.…”
Section: Introductionmentioning
confidence: 99%